Features of studying the category of tense of the verb in schools with the Uzbek language of instruction (Eurasian Journal of Learning and Academic Teaching, 2022)
The task of the subject of the Russian language in schools with the Uzbek language of instruction is the acquisition by students of strong oral and written skills.